Stimulation of Pressure on Liquid Concept in Stad Learning Model to Improve Rational Thinking Skills and Learning Outcomes of Students - A. W. Nuayi; S. Supartin; T. J. Buhungo (Jurnal Pendidikan Fisika Indonesia)
The research aims to determine the effect of using cooperative learning model type STAD on learning science to students’ performance in rational thinking skills and learning outcome. The point of view of this influence is seen from the presence or absence of improvement rational thinking skills activity of cognitive learning outcomes after treatment. The research used experimental method with the design One Shot Case Study and took place in SMPN 3 Gorontalo. The data obtained were students’ performance in rational thinking skill and learning outcome gathered by observation sheet of students’ activity and test sheet. The result show that increase in average score of students’ performance in rational thinking in the third meeting compared to the first meeting by indicators of information digging, information processing, problem solving, and conclusion formulating. The overall result shows that the students’ performance in rational thinking skills achieves good criteria; additionally, the students’ learning outcomes achieve average score of 83.81, categorized as B (good).